Zoe Baumann: capstone - Baumann, Zoe, artist (Colorado State University. Libraries, 2022)
The artist's statement: My name is Zoe and I'm a graphic designer and video artist based out of Fort Collins, CO. I am a lover of the intersection of art and music, specializing in band merchandise and branding as well as music videos and live video synthesis for concerts. I am interested in how the intersection of art and music comes together to create a visceral experience and community engagement for its viewers. I take inspiration from art movements such as art nouveau, surrealism, folk art, op art, and many others to create my artistic lexicon. While my inspirations are centuries old, I strive to keep my work feeling contemporary and fresh through a high-contrast graphic style. It's important to me to pay homage to the long and beautiful history of design, as I feel a connection to its humanity and decorative elements. My design methodology starts with the concept, where I first research to understand my aesthetic goals and historical references. I then consider the necessary steps to take for the final product, particularly the dimensions needed for web or print, the necessary information, and the compositional hierarchy. Throughout the design process, I keep an intuitive workflow while paying close attention to color theory, composition, and cohesive typography. When working with clients, I make sure to keep them involved throughout the process so that everyone is heard and on the same page. The last steps of fine-tuning, printing, and sending the work off are my favorite, as I get to see the final outcome and its eventual real-life applications. My graphic design practice is guided by the intersection of art and music and modernizing vintage design movements. My methodology consists of intentional and well-researched decisions, informed by conversations with clients and my personal design sensibilities.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design